Sin1-mediated mTOR signaling in cell growth, metabolism and immune response. Issue 6 (19th November 2019) - Ruan, Chun; Ouyang, Xinxing; Liu, Hongzhi; Li, Song; Jin, Jingsi; Tang, Weiyi; Xia, Yu; Su, Bing
Abstract: The mammalian target of rapamycin (mTOR) is an evolutionarily conserved Ser/Thr protein kinase with essential cellular function via processing various extracellular and intracellular inputs. Two distinct multi-protein mTOR complexes (mTORC), mTORC1 and mTORC2, have been identified and well characterized in eukaryotic cells from yeast to human. Sin1, which stands for S ty1/Spc1- in teracting p rotein1, also known as mitogen-activated protein kinase ( MAPK ) a ssociated p rotein (MAPKAP)1, is an evolutionarily conserved adaptor protein. Mammalian Sin1 interacts with many cellular proteins, but it has been widely studied as an essential component of mTORC2, and it is crucial not only for the assembly of mTORC2 but also for the regulation of its substrate specificity. In this review, we summarize our current knowledge of the structure and functions of Sin1, focusing specifically on its protein interaction network and its roles in the mTOR pathway that could account for various cellular functions of mTOR in growth, metabolism, immunity and cancer.